2022
DOI: 10.1101/2022.12.12.22283340
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Suicide after leaving the UK Armed Forces 1996-2018: a cohort study

Abstract: Background: There are comparatively few international studies investigating suicide in military veterans and no recent UK studies. We aimed to investigate the rate, timing, and risk factors for suicide in personnel who left the UK Armed Forces (UKAF) over a 22-year period. Methods and findings: We conducted a retrospective cohort study of suicide in personnel who left the regular UKAF between 1996 and 2018 by linking national databases of discharged personnel and suicide deaths. Of the 458,058 individuals who … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…It is an established finding that suicides are lower in serving members of the armed forces compared to members of the general population [15].It may be due to the "healthy worker effect"; people in employment generally, and especially in physically demanding jobs like the armed forces, are less likely than the general population to be ill or disabled. In the England, recent work has shown that veterans are at no greater risk of suicide than the general population [16]. Our sample will likely capture individuals who since the time of 2011 Census are now veterans, as well as those who remained serving members at the end of study.…”
Section: Discussionmentioning
confidence: 99%
“…It is an established finding that suicides are lower in serving members of the armed forces compared to members of the general population [15].It may be due to the "healthy worker effect"; people in employment generally, and especially in physically demanding jobs like the armed forces, are less likely than the general population to be ill or disabled. In the England, recent work has shown that veterans are at no greater risk of suicide than the general population [16]. Our sample will likely capture individuals who since the time of 2011 Census are now veterans, as well as those who remained serving members at the end of study.…”
Section: Discussionmentioning
confidence: 99%
“…16 The study also reported that ex-serving personnel with a shorter length of service (<10 years of service) were at increased risk. 16 Protective factors for self-harm and suicide behaviours among the military community have been less frequently explored than risk factors, but include social support 18,3436 , higher educational attainment 37 , employment 38 and holding a more senior rank during service (e.g. officer) 18,19,39 .…”
Section: Introductionmentioning
confidence: 92%
“…medical discharge). 31,32 Additionally, younger age is a risk factor 16,31,33 , with one recent study from the United Kingdom (UK) reporting that suicide risk was two to three times higher in men and women under 25 years old who had left the UK Armed Forces (compared to the general population). 16 The study also reported that ex-serving personnel with a shorter length of service (<10 years of service) were at increased risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Factors that are associated with risk of suicide in veterans include being a young male veteran (under 28 years), discharging as an early service leaver (ESL) (within 4 years of enlistment), being an older (over 40 years) female veteran, or having depression or alcohol problems. [7][8][9] The literature also suggests that veterans who experienced adverse life events before enlisting or who have difficulties adjusting to civilian life may be at higher risk. 10 Currently, there is a scarcity of research on suicide prevalence and risk in veterans within a…”
Section: Introductionmentioning
confidence: 99%